Civil Society Criticism and State Response: Democracy Issues in Indonesia’s Counter-Terrorism Experience - Harahap, Husnul Isa; Rauf, Maswadi (Research Journal in Advanced Humanities, 2025)
Terrorist attacks in various countries have triggered a policy of war on terrorism. The Indonesian government has also done the same thing to defeat terrorists and has succeeded in reducing acts of terror. However, this step received criticism from civil society. This study analyzes the scope of the arguments of the criticism and analyzes the state’s response to the criticism. In addition, it also analyzes the issues of democracy in Indonesia that emerged in the counterterrorism debate. This study uses qualitative methods, and data sources are collected from books, journals, documents, photos, audio and video recordings, and interview data combined with qualitative analysis methods. This study has three main findings. First, criticism of counterterrorism from Civil Society covering arguments about security issues, professionalism, violations of the law, issues of transparency, accountability and justice, as well as improvements in quality. Second, the state responds to Civil Society criticism through two expressions: (1) accepting some of the criticism from Civil Society to improve counterterrorism institutions and (2) rejecting some criticism from Civil Society because terrorism cases are complicated to resolve. Third, there are five democracy issues related to the counterterrorism debate in Indonesia, including (1) the issue of excessive restrictions on authority, (2) respect for human rights, (3) freedom, (4) equality before the law and justice, and (5) the issue of military involvement.